Utilitarianisme dan Keseimbangan Antara Kepentingan Umum dan Kepentingan Individu - Hananto, V. Andri (Jurnal Hukum IUS QUIA IUSTUM, 2025)
One of the most influential schools of legal thought in the world is Utilitarianism. Utilitarianism is built upon the famous maxim of its pioneer, Jeremy Bentham, "the greatest happiness for the greatest number". The core of Bentham's utilitarian teaching focuses on the quantitative aspect of benefits for the general public. The concept of quantitative thinking is the main strength of Bentham's utilitarian theory as it produces legal impartiality, but this concept also brings the greatest criticism, with the emergence of views that utilitarianism does not take into account the balance of individual and societal interests. This is a doctrinal research that aims to explore the history of the birth of utilitarianism, its core teachings, development, and, criticism, as well as the refinement of utilitarianism, especially related to the issue of balance between public and individual interests. The results of this study conclude that the problem of the balance of public and individual interests in utilitarianism is mainly caused by the combination of the consequentialist and aggregative characters of utilitarianism. There have been attempts to be overcome such imbalance with the birth of rule utilitarianism and indirect utilitarianism as well as social choice theory and the capability approach.Keywords: Balance, Public Interest, Individual Interest, Utilitarianism AbstrakSalah satu aliran pemikiran hukum yang sangat berpengaruh di dunia adalah Utilitarianisme. Utilitarianisme dibangun berdasarkan maxim yang sangat terkenal dari pelopornya, Jeremy Bentham, “the greatest happines for the greatest number”. Inti ajaran utilitas Bentham berfokus pada aspek kuantitas kemanfaatan bagi masyarakat umum. Konsep pemikiran kuantitatif merupakan kekuatan utama dari teori utilitarianisme Bentham karena menghasilkan imparsialitas hukum, namun konsep tersebut juga mendatangkan kritik terbesar, dengan munculnya pandangan yang menyatakan utilitarianisme tidak memperhitungkan keseimbangan kepentingan individu dan masyarakat. Penelitian ini merupakan penelitian doktrinal dan bertujuan untuk mengetahui sejarah lahir, inti ajaran, perkembangan, dan, kritik, serta penyempurnaan utilitarianisme, khususnya terkait dengan isu keseimbangan antara kepentingan umum dan individu. Hasil penelitian ini menyimpulkan bahwa persoalan keseimbangan kepentingan umum dan individu dalam utilitarianisme terutama disebabkan karena perpaduan karakter konsekuensialis dan agregatif utilitarianisme dan telah coba diatasi dengan lahirnya rule utilitarianism dan indirect utilitarianism serta teori pilihan sosial dan capability approach.Kata Kunci: Keseimbangan, Kepentingan Umum, Kepentingan Individu, Utilitarianisme